2017
DOI: 10.1016/j.ejop.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Sea-ice eukaryotes of the Gulf of Finland, Baltic Sea, and evidence for herbivory on weakly shade-adapted ice algae

Abstract: To determine community composition and physiological status of early spring sea-ice organisms, we collected sea-ice, slush and under-ice water samples from the Baltic Sea. We combined light microscopy, HPLC pigment analysis and pyrosequencing, and related the biomass and physiological status of sea-ice algae with the protistan community composition in a new way in the area. In terms of biomass, centric diatoms including a distinct Melosira arctica bloom in the upper intermediate section of the fast ice, dinofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…Cells are round or elongated, ~ 7 µ m in diameter or 10 µ m long, respectively (Figure 7H). Chlamydomonas is a common genus found in the Arctic during the spring and summer months (Balzano et al, 2012; Lovejoy et al, 2002), that can occur in association with sea-ice (Majaneva et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells are round or elongated, ~ 7 µ m in diameter or 10 µ m long, respectively (Figure 7H). Chlamydomonas is a common genus found in the Arctic during the spring and summer months (Balzano et al, 2012; Lovejoy et al, 2002), that can occur in association with sea-ice (Majaneva et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The nucleus, stigma and two 7 µ m flagella can be observed (Figure 7L). Although mainly isolated from coastal and estuarine environments (Bendif et al, 2013), this genus has also been reported as characteristic of sea-ice environments (Majaneva et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the biomass plankton algae dynamics from January to April in Kandalaksha Bay also revealed the highest values in April [50]. The values of Chl a concentration obtained in the under-ice water of the White Sea are comparable to those in the under-ice water of the Baltic Sea in March (0.5-1.0 µg L −1 ) [51].…”
Section: Discussionmentioning
confidence: 84%
“…These centric diatoms are supplemented by large contributions of Melosira arctica and the cyanobacterium Aphanizomenon sp. that can predominate abundances in the brine channels (Majaneva et al 2017). In contrast to Arctic and Antarctic sea ice communities, dinoflagellates and green algae contribute to a large fraction of the biomass in Baltic Sea ice and open water (Kaartokallio et al 2007;Piiparinen et al 2010).…”
Section: Microalgaementioning
confidence: 99%